2022
DOI: 10.1161/hypertensionaha.121.18477
|View full text |Cite
|
Sign up to set email alerts
|

DPP4 Promotes Human Endothelial Cell Senescence and Dysfunction via the PAR2–COX-2–TP Axis and NLRP3 Inflammasome Activation

Abstract: Background: Abnormal accumulation of senescent cells in the vessel wall leads to a compromised vascular function contributing to vascular aging. Soluble DPP4 (dipeptidyl peptidase 4; sDPP4) secretion from visceral adipose tissue is enhanced in obesity, now considered a progeric condition. sDPP4 triggers vascular deleterious effects, albeit its contribution to vascular aging is unknown. We aimed to explore sDPP4 involvement in vascular aging, unraveling the molecular pathway by which sDPP4 acts on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 54 publications
0
10
0
1
Order By: Relevance
“…Subsequently, DPP4 was implicated in alleviating metabolism-related diseases like obesity, chronic liver disease, and atherosclerosis (53)(54)(55)(56). Interestingly, DPP4 inhibitors have been proven effective at reducing atherosclerosis in mice independently of their canonical impact on glucose metabolism, suggesting that DPP4 has important functions in non-metabolic tissues and cells (13,57). As mentioned, recent studies have identified DPP4 on the surface of senescent cells, and soluble DPP4 was found to trigger endothelial senescence, demonstrating that DPP4 may contribute to the development of the senescent phenotype (11,57).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, DPP4 was implicated in alleviating metabolism-related diseases like obesity, chronic liver disease, and atherosclerosis (53)(54)(55)(56). Interestingly, DPP4 inhibitors have been proven effective at reducing atherosclerosis in mice independently of their canonical impact on glucose metabolism, suggesting that DPP4 has important functions in non-metabolic tissues and cells (13,57). As mentioned, recent studies have identified DPP4 on the surface of senescent cells, and soluble DPP4 was found to trigger endothelial senescence, demonstrating that DPP4 may contribute to the development of the senescent phenotype (11,57).…”
Section: Discussionmentioning
confidence: 99%
“…These effects are reduced by pharmacological NLRP3 inhibitors and in NLRP3 deficient mice. 60,63,64 These processes are also associated with redox control of NLRP3 assembly/activation. Of importance overexpression of an ELABELA (endogenous ligand of the aapelinpelin receptor) ameliorated blood pressure and renal damage via reduction in Nox-derived ROS and inflammasome activation in deoxycorticosterone acetate-salt rats.…”
Section: Inflammatory Mechanisms Of Microvascular Damagementioning
confidence: 99%
“…C1q/tumor necrosis factor-related protein 9 (CTRP9), an emerging potential cardiokine, contributes to the inhibition of hyperglycemia-induced endothelial senescence through an AMPKα/ Krüppel-like factor 4 (KLF4)-dependent signaling pathway [ 143 ]. Soluble dipeptidyl peptidase 4 (DPP4), secreted from visceral adipose tissue, induces EC senescence through the protease-activated receptor 2 (PAR2)–cyclooxygenase2 (COX-2)–thromboxane receptor (TP) axis and activates the NLRP3 inflammasome [ 144 ]. In cultured HAECs, senescence induced by apoC3-rich low-density lipoprotein (AC3RL) is mediated by intracellular ROS formation, H2A.X variant histone (H2AX) deposition, and F-box only protein 31 (FBXO31) activation, resulting in the inhibition of mouse double minute 2 homolog (MDM2), p53, and p21 activation [ 145 ].…”
Section: Molecular Players and Pathways Associated With Endothelial C...mentioning
confidence: 99%